2001
DOI: 10.1021/ja003518b
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of VX, GB, GD, and HD with Nanosize Al2O3. Formation of Aluminophosphonates

Abstract: Room-temperature reactions of VX, GB, GD, and HD with nanosize Al(2)O(3) (AP-Al(2)O(3)) have been characterized by (31)P, (13)C, and (27)Al MAS NMR. Nerve agents VX, GB, and GD hydrolyze to yield surface-bound complexes of their corresponding nontoxic phosphonates. At sufficiently high loadings, discreet aluminophosphonate complexes, Al[OP(O)(CH(3))OR](3), are generated which are identical to synthesized model compounds. Thus the reaction with phosphonic acids is not just surface-limited, but can continue to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
252
0
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 318 publications
(274 citation statements)
references
References 28 publications
13
252
0
3
Order By: Relevance
“…Bulk quantities of pure alumina are accessible only through high temperature syntheses [9]. Precedents of powdered nanoalumina formation from aluminum ethoxide [10], aluminum tri-tert-butoxide [11], aluminum isopropoxide and aluminum tributoxide precursors exist in the literature. These studies have shown that variation of starting material, type and amount of solvent and stirring time have an effect on the surface properties of the alumina.…”
Section: Introductionmentioning
confidence: 99%
“…Bulk quantities of pure alumina are accessible only through high temperature syntheses [9]. Precedents of powdered nanoalumina formation from aluminum ethoxide [10], aluminum tri-tert-butoxide [11], aluminum isopropoxide and aluminum tributoxide precursors exist in the literature. These studies have shown that variation of starting material, type and amount of solvent and stirring time have an effect on the surface properties of the alumina.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, reports have revealed that there is a great interest in use of solid sorbent decontaminants, such as nano metal oxides. Several nanocrystalline metal oxides, such as CaO [5], MgO [6][7][8], Al 2 O 3 [6][7][8][9], and ZnO [10], have been synthesized as adsorbents and catalysts using in various scientific fields. One of the most notable fields is their utilization for multiple defense applications, such as nuclear, biological, chemical (NBC) warfare, destructive adsorption, and decomposition of acid gases and polar organics, including CWAs and their mimics [11][12][13].…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
“…The control of particle size and the morphology of the oxide are of crucial importance nowadays both from the fundamental and industrial point of view 2 . The mixed metal oxides prepared from heterometallic-µ-oxoalkoxides [3][4][5][6] have been used for absorbing harmful chemicals 7 and gases such as SO 2, CCl 4 and decontaminating chemical warfare agents 8 . The alkaline earth metal titanates like barium titanate, calcium titanate (CaTiO 3 ), strontium titanate (SrTiO 3 and Ba x Sr 1-x TiO 3 ) due to their exceptional properties expose potential applications in multilayer ceramic capacitors, electro-optic, dielectric and piezoelectric devices [9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%